2021
DOI: 10.1007/s11033-021-06510-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of cytoskeleton remodeling proteins and their mRNA expression in tumor tissue of metastatic laryngeal and hypopharyngeal cancers

Abstract: Actin-binding proteins (ABPs) and various signaling systems are involved in the process of squamous cell carcinoma of the larynx and hypopharynx (SCCLH) metastasis. The clinical significance of these proteins has not yet been determined. We analyzed the relationship between the mRNA levels of cofilin 1 (CFL1), profilin 1 (PFN1), adenylyl cyclase-associated protein 1 (CAP1), SNAI1 and RND3 and SCCLH metastasis. The serum levels of the above ABPs were estimated and the relationship between them and their mRNA ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The spleen is the largest immune organ, and the data indicated that the CFL1 gene may be involved in mammalian cellular immunity and affect the development of tumors. This result is consistent with a previous report that the CFL1 gene can participate in cancer development [21,22]. However, the expression level of the CFL1 gene in adipose tissues was almost unchanged between calf and adult cattle, and the results suggested that the CFL1 gene was not involved in the regulatory mechanism of growth and differentiation during cattle adipose tissue development.…”
Section: Discussionsupporting
confidence: 92%
“…The spleen is the largest immune organ, and the data indicated that the CFL1 gene may be involved in mammalian cellular immunity and affect the development of tumors. This result is consistent with a previous report that the CFL1 gene can participate in cancer development [21,22]. However, the expression level of the CFL1 gene in adipose tissues was almost unchanged between calf and adult cattle, and the results suggested that the CFL1 gene was not involved in the regulatory mechanism of growth and differentiation during cattle adipose tissue development.…”
Section: Discussionsupporting
confidence: 92%
“…There is also evidence of the involvement of CAP1 in signaling pathways [ 9 , 11 12 ] and caveolin-dependent endocytosis, in particular, in the internalization of low-density lipoprotein receptor (LDLR) and low density lipoprotein receptor-related protein (LRP) [ 13 14 ] . Recently, there have also been a number of studies suggesting that CFL1 and CAP1 work in conjunction to influence the aggressiveness of tumor development [ 10 , 12 , 14 15 ] .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the genes encoding fascin (FSCN1), ezrin (EZR), and adenylyl cyclase associated protein 1 (CAP1) are involved in the development of HNSCC [14]. The prognostic signi cance of determining the content of pro lin 1 (PFN1) and CAP1 in the blood serum in relation to the development of lymph node metastases was shown [15]. FSCN1 was associated with cancer development in patients with premalignant laryngeal and hypolaryngeal lesions [14].…”
Section: Introductionmentioning
confidence: 99%